PENGEMBANGAN MEDIA SIMULASI MENGGUNAKAN MACROMEDIA FLASH PADA PEMBELAJARAN IPA FISIKA KELAS IX PADA MATERI SISTEM TATA SURYA - Putri, Nur Suci Eka; Yulkifli, Yulkifli; Haris, Venny (Jurnal Pembelajaran MIPA, 2014)
Media development simulation is one of the alternatives to address the problem of learning physics that seem abstract and difficult, and can overcome the limitations of the tools in the school laboratory. This research is a development that consists of 3 phases: phase define (definition), design (design), and develop (development). The development of research instruments using validation sheet, observation sheets, and student questionnaire responses. Prototype 2 is validated by experts from STAIN Batusanggkar Physical Education and 1 teacher MTs N 1 Lawang Mandahiling. At this stage of the practicalities, Media piloted simulations in MTs N 1 Mandahiling Lawang to see the practicality of media simulation has been designed. Media as valid and practical to meet the criteria for the level of validity and practicality. Results showed that media simulation on the solar system material is very practical and very valid (validity include content, presentation, language and readability) from the point of view of experts Physical Education and one junior high school teacher.Key words : development, media simulation, macromedia flash, solar system